The impact of human capital on college students’ employment outcomes: The mediating role of students’ perceived employability - Fei, Hongxia; Ghazali, Abdul Jalil Bin; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of human capital on college students’ employment outcomes in Shanxi Province, China, with a focus on the mediating role of perceived employability. Based on Human Capital Theory and Social Cognitive Career Theory, a structural equation model was used to analyze data from 750 valid questionnaires. Findings reveal that human capital, encompassing academic performance, skills, and work experience, significantly and positively affects both perceived employability and employment outcomes. Perceived employability not only directly influences employment outcomes but also mediates the relationship between human capital and employment outcomes, with a partial mediating effect confirmed by empirical tests. The study enriches theoretical perspectives on the interplay between human capital, perceived employability, and employment outcomes. Practical implications include recommendations for colleges to enhance students’ employability through targeted curriculum design, practical training, and career guidance programs. This research provides valuable insights for policymakers and educators aiming to address regional disparities and optimize talent development strategies in transitional economies.